∫ 0 ∞ 3 x − 1 x 3 d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Shouldn't it be (3^x - 1) instead of (3^x + 1)?
Log in to reply
Thank you for pointing out the typo. I solved it the right way but typed the integrand with the wrong sign. It is now corrected.
I = ∫ 0 ∞ 3 x − 1 x 3 d x = ln 4 3 1 ∫ 0 ∞ e u − 1 u 3 d u = ln 4 3 ζ ( 4 ) Γ ( 4 ) = 9 0 ln 4 3 π 4 3 ! ≈ 4 . 4 5 7 9 Let u = x ln 3 ⟹ d u = ln 3 d x where ζ ( ⋅ ) is the Riemann zeta function and Γ ( ⋅ ) is the gamma function
References:
Problem Loading...
Note Loading...
Set Loading...
Consider the integral:
I = ∫ 0 ∞ 3 x − 1 x 3 d x ⟹ I = ∫ 0 ∞ 1 − 3 − x x 3 3 − x d x
Recognising that as x > 0 :
1 − 3 − x 3 − x = k = 1 ∑ ∞ 3 − k x
Therefore:
I = ∫ 0 ∞ x 3 ( k = 1 ∑ ∞ 3 − k x ) d x
Let: x ln 3 = z . This substitution transforms the integral to:
I = ( ln 3 ) 4 1 ∫ 0 ∞ z 3 ( k = 1 ∑ ∞ e − k z ) d z
I = ( ln 3 ) 4 1 ∫ 0 ∞ z 3 ( e − z + e − 2 z + e − 3 z + … ) d z
Now, consider the integral:
J ( k ) = ∫ 0 ∞ z 3 e − k z d z Taking k z = t transforms the integral to:
J ( k ) = k 4 1 ∫ 0 ∞ t 3 e − t d t ⟹ J ( k ) = k 4 1 Γ ( 4 ) J ( k ) = k 4 6
Since Γ ( n + 1 ) = n ! . Using the above result transforms I as follows:
I = ( ln 3 ) 4 1 ( J ( 1 ) + J ( 2 ) + J ( 3 ) + … ) ⟹ I = ( ln 3 ) 4 6 ( k = 1 ∑ ∞ k 4 1 )
⟹ I = ( ln 3 ) 4 6 9 0 π 4 ⟹ I = 1 5 ( ln 3 ) 4 π 4 ≈ 4 . 4 5 8
This is because as per the definition of the Reimann-Zeta function:
k = 1 ∑ ∞ k 4 1 = 9 0 π 4